Avaliação de balanceamento de linha em linha de bandagem de estatores bobinados - Pommerening, Ailton (2020)
In a highly competitive market, companies are increasingly seeking to obtain advantages through their internal processes. Good labor management is of paramount importance for controlling expenses, as these have a strong impact on the cost of processing products. The present work had the objective of evaluating the production of a banding line of coiled stators from one of the 10 existing lines in the department and Manufacturing I of WEG Motores, using an MTM tool (Methods-Time Measurement). MTM was used for the description, structuring, configuration and planning of work systems and consequently an efficient production system standard. This study is an observation in the study environment, with observation by the researcher and analysis of data and environment which intends to propose changes and layout improvements through the kaizen philosophy. The method used will be the bibliographic based on scientific articles and books that explore the subject with well-known and renowned authors. The challenge was great, as the work had a direct impact on employees with the proposal to reduce the staff of the respective line by 33%, adapting productivity to the current demand of the coiled stators of this production line. With the proposal implemented in the winding section, the Factory obtains a real gain, as it will not need to hire new labor to cover other jobs in other production lines, with this there is a significant reduction in transformation costs, leaving the most competitive products on the market.